SAT0343 Severe prevalent vertebral fractures predict subsequent vertebral and non-vertebral fractures: A 3-year prospective study. (23rd January 2014) - Bruyere, O.; Roux, C.; Nicolet, D.; Fechtenbaum, J.; Deroisy, R.; Reginster, J.-Y.
Abstract : Objectives: To examine whether a prevalent severe vertebral fracture predicts subsequent fracture and to assess the effect of strontium ranelate to reduce fracture in patients with such prevalent severe vertebral fracture. Methods: Analysis of two 3-year randomized controlled trials investigating the clinical effect of strontium ranelate. Vertebral and major non-vertebral fractures (i.e. ribs sternum, wrist region, pelvic sacrum, collarbone, humerus, proximal femur) were assessed during the 3 years. At baseline on standard radiographs, each vertebra received a severity grade corresponding to either no fracture either a mild, moderate or severe fracture based on a semi-quantitative visual assessment. All women received calcium and vitamin D during the whole length of the study. Results: 6137 women aged mean (SD) 75.1 (6.1) years were included in this study. In the placebo group, after 3 years of follow-up, 43% of the women with a prevalent severe vertebral fracture had experienced a new vertebral fracture compared to only 12.5% of the women without any vertebral fracture (OR 3.46 [2.87-4.18]). The logistic regression analysis, adjusted for age, body mass index, femoral neck bone mineral density and number of prevalent vertebral fractures, showed that the presence of a severe vertebral fracture was significantly associated with new vertebral fractures over a 3-year follow-up period. In women with severe prevalent vertebral fracture (N=680), strontium ranelate was able to significantly reduce the risk of new vertebral fractures (OR 0.75 [0.61-0.91]). Conclusions: In summary, severe prevalent vertebral fracture is an independent predictor of new vertebral and non-vertebral fractures that could be taken into account in fracture risk management. Disclosure of Interest: O. Bruyere Grant/Research support from: Servier, C. Roux: None Declared, D. Nicolet: None Declared, J. Fechtenbaum: None Declared, R. Deroisy: None Declared, J.-Y. Reginster: None Declared